UPAYA PENINGKATAN KEMAMPUAN GURU MATA PELAJARAN MUATAN NASIONAL DALAM MERANCANG RENCANA PELAKSANAAN PEMBELAJARAN (RPP) DAN MELAKSANAKAN PEMBELAJARAN MELALUI SUPERVISI DI SMK NEGERI 1 TIMPEH - Sugiyono Sugiyono (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This school action research aims at describing teachers’ ability on national contents curriculum, consist of religion, budi pekerti, civic education, Indonesian Language, English, mathematic, and Indonesian history on designing lesson plans and doing learning process in the classroom. These activities were observed by supervisor. This research did at SMKN 1 Timpeh. It did with two cycles and each cycle had same stages, namely planning, acting, observing, and reflecting. Then each stage consisted of two meetings. First meeting focused on lesson plan and second meeting focused on learning process. Data of this research were got through observation sheets. These observation sheets were used to evaluate or analyse the lesson plans and evaluate teachers’ application during learning process. These instruments were presented through tables of assessing results of interpreting scores and analysed qualitatively. Result of this study shows that teachers’ ability to create the lesson plans with an average score of 87.3. This score belongs to good category. Meanwhile, the ability to implement learning in class is 87.7. This score belongs to good category. It can be said that teachers’ ability to design the lesson plans and doing learning process improve.